At the wheel of research: an exclusive biography of Dr. Soumya Swaminathan - Mascarenhas, Anuradha (New Delhi Bloomsbury, 2024)
Think out of the box, ask questions, trust science and find solutions - this inspiring book captures Dr Soumya Swaminathan's incredible journey in science. With interesting life experiences, practical learnings and insights on leveraging research to benefit patient care, this is a biography which will be read by layman and scientist alike.
Keywords: Biography- Dr. Soumya Swaminathan